Clinical effects from household insecticide: pyrethroid or organophosphate toxicity?. Issue 11 (21st November 2019) - Basrai, Zahir; Koh, Cynthia; Celedon, Manuel; Warren, Jonathan
Abstract : A 54-year-old man with a history of schizophrenia presented to the emergency room for weakness with associated lacrimosis, drooling, nausea, emesis, diarrhoea, diplopia and burning sensation on his skin that began 6 hours after spraying five cans of Raid on his carpet. He was noted to have miotic pupils and hyperactive bowel sounds. Given the clinical presentation, the patient was diagnosed with organophosphate (OP) toxicity. After being admitted, he developed symptoms associated with his OP toxicity and was successfully treated with atropine and pralidoxime. Most Raid products contain pyrethroids; however, both OPs and pyrethroids are available in commercial pesticides and patients may misidentify ingestions. There are limited data reporting the toxicity of pyrethroid overdose in humans and to guide its subsequent treatment. It is crucial to keep a low threshold for diagnosing and treating patients with acute onset of symptoms suspicious for an OP or pyrethroid toxidrome.